Tunica Albuginea Urethroplasty for Panurethral Strictures - Mathur, Raj K; Sharma, Adittya K (Urology Journal, 2010)
Purpose: To assess the efficacy of tunica albuginea urethroplasty for pan urethral stricture management as an alternative approach to conventional dorsal buccal mucosal graft urethroplasty, especially in cases with unavailability of healthy buccal mucosa.Materials and Methods: Eighty-six patients with panurethral strictures underwent tunica albuginea urethroplasty at our center with follow-ups at 6, 12, 24, and 36 months. Results were assessed by comparative analysis of preoperative and postoperative patient’s satisfaction (based on symptoms) alongwith retrograde urethrography, urethrosonography, and uroflowmetry. Ten patients from the successful group underwent postoperative urethroscopic examination.Results: Counting good and fair results as successful (satisfied and not requiring revision urethroplasty), success (good + fair) rate was 95.3% at immediate postoperative and at 6 months. Results reduced to 93% at 12 months, 90.7% at 24 months, and 89.5% at the end of 36 month follow-up. Failure (poor results requiring revision urethroplasty) rate was 10.5% at the end of the 3 years of follow-up.Conclusion: Tunica albuginea urethroplasty runs over the concept of urethral groove and the ease of procedure with adequately satisfactory results provides decent outcomes. Tunica albuginea urethroplasty gives advantage of local availability and achieving patent distensible urethra without any graft. Urethroscopy of these subjects, by direct visualization shows the area of roof formed by tunica appears well covered with urothelium, further substantiating its ability to maintain patency and distensibility of the urethra.